Erratum for the “ESSAY REVIEW: Subtle Energies and Quan-tum Mechanics,” which appeared in the Summer 2019 Journal of Scientific Exploration, 33(2), pp. 277–287. - Erickson, Kathleen E. (Journal of Scientific Exploration, 2019)
The Essay Review began by listing the two books under review, where the price for the second book, The Mind’s Interaction with the Laws of Physics and Cosmology by Jeffrey S. Keen, was incorrect, and which is here shown with the correct price of 33.95.